Pengaruh Kinerja ESG Dan Intensitas Energi Terhadap Keuangan Berkelanjutan - Lila Ariana Luky; Etty Murwaningsari (LPPM POLITEKNIK LP3I BANDUNG, 2026)
This study aims to (1) examine the effect of ESG performance on sustainable finance and (2) examine the effect of energy intensity on sustainable finance in companies from the basic materials and consumer non-cyclicals sectors listed on the Indonesia Stock Exchange for the period 2022–2024. To this end, a quantitative approach was employed in the form of panel data regression applied to 135 observations from a total of 45 sample companies. The test results indicate that ESG performance makes a significant positive contribution to sustainable finance, while the relationship with energy intensity tends to be negative but insignificant. These findings simultaneously confirm the relevance of stakeholder theory and legitimacy theory, as well-executed sustainability practices can serve as a signal that a company is stable in the long term. On this basis, companies are advised to integrate ESG strategies as part of their operational efficiency efforts while simultaneously strengthening their legitimacy in the eyes of the public.